2020
DOI: 10.1115/1.4047385
|View full text |Cite
|
Sign up to set email alerts
|

Forced Convection Computational Fluid Dynamics Analysis of Architected and Three-Dimensional Printable Heat Sinks Based on Triply Periodic Minimal Surfaces

Abstract: The drive for small and compact electronic components with higher processing capabilities is limited by their ability to dissipate the associated heat generated during operations, and hence, more advanced heat sink designs are required. Recently, the emergence of additive manufacturing techniques facilitated the fabrication of complex structures and overcame the limitation of traditional techniques such as milling, drilling, and casting. Therefore, complex heat sink designs are now easily realizable. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(23 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Neben der durch Wasser gekühlten Anwendung wurden mit dem gleichen Zelltyp auch experimentelle Versuche im Windkanal durchgeführt und die Wärmeübertragung mit herkömmlichen Kühlrippen verglichen [59]. Erzwungene Konvektion ist ebenfalls Thema der Veröffentlichung von AL-KETAN et al [60]. Sie vergleichen Strömungs-und Wärmetransporteigenschaften von TPMS-Zellen (Gyroid und Diamant) mithilfe von Strömungssimulationen.…”
Section: Wärmeübertragungunclassified
“…Neben der durch Wasser gekühlten Anwendung wurden mit dem gleichen Zelltyp auch experimentelle Versuche im Windkanal durchgeführt und die Wärmeübertragung mit herkömmlichen Kühlrippen verglichen [59]. Erzwungene Konvektion ist ebenfalls Thema der Veröffentlichung von AL-KETAN et al [60]. Sie vergleichen Strömungs-und Wärmetransporteigenschaften von TPMS-Zellen (Gyroid und Diamant) mithilfe von Strömungssimulationen.…”
Section: Wärmeübertragungunclassified
“…However, strut-based lattice structures have a high-stress concentration at strut junctions [ 36 ], while TPMS structures provide smooth and continuous surfaces. Moreover, the heat transfer coefficient and effective thermal conductivity of TPMS structures are also significantly higher than strut-based lattice structures [ 37 , 38 ], because of their continuous surface patterns. The study of heat transfer from pin-fin heat sinks demonstrated that thin-walled structures of TPMS lattices had high performance in heat dissipation [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently geometries with minimal surfaces have been reported in the literature and referred to as triply periodic minimal surfaces (TPMSs). [13][14][15][16] The mean curvature of these surfaces is zero at all points on the surface. These surfaces can also have infinite periodicity and can extend in three dimensions forming interpenetrating composites having 3-3 connectivity thus improving their effective properties.…”
Section: Introductionmentioning
confidence: 99%